Corporate social responsibility and credit rating around the world: The role of societal trust. Issue 4 (7th August 2022) - Chang, Kiyoung; Li, Ying; Shim, Hyeongsop
Abstract: We hypothesize that societal trust alleviates moral hazard concerns that undermine credit rating agencies' perceived value of corporate social responsibility (CSR). We test our hypothesis using a large global sample and find a more salient relationship between CSR and credit rating only in countries with high societal trust. Our findings reconcile the mixed empirical worldwide evidence on this relationship. Additional tests provide further evidence that it is societal trust, not other country‐level factors, that drives our results.